Effect of systemic transplantation of bone marrow‐derived mesenchymal stem cells on neuropathology markers in APP/PS1 Alzheimer mice. (19th April 2016) - Naaldijk, Y.; Jäger, C.; Fabian, C.; Leovsky, C.; Blüher, A.; Rudolph, L.; Hinze, A.; Stolzing, A.
Abstract : Aims: Mesenchymal stem cells (MSC) have recently attracted interest as a potential basis for a cell‐based therapy of AD. We investigated the putative immune‐modulatory effects in neuroinflammation of systemic transplantation of MSC into APP/PS1 transgenic mice. Methods: 10 6 MSC were injected into APP/PS1 mice via the tail vein and histological analysis was performed for microglia and amyloid (pE3‐Aβ) plaque numbers, glial distribution and pE3‐Aβ plaque size. In addition, a biochemical analysis by qPCR for pro‐inflammatory, chemoattractant and neurotrophic factors was performed. Results: MSC are associated with pE3‐Aβ plaques. The effects of transplantation on microglia‐associated pathology could be observed after 28 days. Animals showed a reduction in microglial numbers in the cortex and in microglia size. Gene expression was reduced for TNF‐α, IL‐6, MCP‐1, and for NGF, in MSC recipients. Also, we investigated for the first time and found no changes in expression of IL‐10, CCR5, BDNF, VEGF and IFNγ. PTGER2 expression levels were increased in the hippocampus but were reduced in the cortex of MSC recipients. While there were no transplant‐related changes in pE3‐Aβ plaque numbers, a reduction in the size of pE3‐Aβ plaques was observed in the hippocampus of transplant recipients. Conclusion: This is the first study to show reduction in pE3‐Aβ plaque size. pE3‐Aβ plaques have gained attention as potential key participants in AD due to their increased aggregation propensity, the possibility for the initial seeding event, resistance against degradation and neurotoxicity. These findings support the hypothesis that MSC‐transplants may affect AD pathology via an immune‐modulatory function that includes an effect on microglial cells. Abstract : Systemically administered mesenchymal stem cells can localise to the brain, reduce the size of Aβ deposits and modulate immune mechanisms in a mouse model of Alzheimer's disease.